2016
DOI: 10.1007/s11864-016-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Palliative Care and Oncologic Care in Non-Small-Cell Lung Cancer

Abstract: Opinion statementPalliative care integrated into standard medical oncologic care will transform the way we approach and practice oncologic care. Integration of appropriate components of palliative care into oncologic treatment using a pathway-based approach will be described in this review. Care pathways build on disease status (early, locally advanced, advanced) as well as patient and family needs. This allows for an individualized approach to care and is the best means for proactive screening, assessment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 149 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Early identification of distress associated with death anxiety and its determinants could allow proactive interventions to be introduced to alleviate and prevent such distress. 1,53,54 In that regard, in a large randomized controlled trial with patients with metastatic cancer, death anxiety was shown to be responsive to a brief psychotherapeutic intervention (Managing Cancer and Living Meaningfully [CALM]). 1 Such an intervention may also alleviate demoralization and enhance engagement in meaningful activities to foster resilience and combat the intrusive effects of the disease on quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early identification of distress associated with death anxiety and its determinants could allow proactive interventions to be introduced to alleviate and prevent such distress. 1,53,54 In that regard, in a large randomized controlled trial with patients with metastatic cancer, death anxiety was shown to be responsive to a brief psychotherapeutic intervention (Managing Cancer and Living Meaningfully [CALM]). 1 Such an intervention may also alleviate demoralization and enhance engagement in meaningful activities to foster resilience and combat the intrusive effects of the disease on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Death anxiety in this population is associated with demoralization and illness intrusiveness highlighting the need for integrated interventions that address physical and psychological well-being. 54 Further research is also needed on the psychological impact of brain metastases and the determinants of death anxiety in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…The mean interval from the first to the second primary tumor ranges from 59 to 62 mo[ 192 ]. Early management of these relapses, whether curative or palliative intent, is associated with better survival and QoL, which underscores the importance of close follow-up[ 193 , 194 ]. For the assessment of treatment-related toxicity and recurrence, we recommend the following follow-up measures.…”
Section: Follow-up (After Sbrt Early Stage and Locally Advanced)mentioning
confidence: 99%
“…More than 25% lung cancer patients suffer from either depression or anxiety, most frequently seen at the time of diagnosis, due to treatment-related misconceptions, on disease progression and near the end of life. Along with psychiatric disorders, social aspects, including poor support system, loss of independence, financial burden, and misinformation regarding prognosis and treatment options, 18 are seen more frequently among elderly when compared with their younger counterparts. It is important to not only evaluate physical wellbeing but also access the psychosocial factors among elderly NSCLC patients.…”
Section: Challenges In Elderly Populationmentioning
confidence: 99%